The effects of human resource management practices on employees’ organisational commitment. - Aladwan, K.; Bhanugopan, R.; D'Netto, Brian (Emerald, 2015)
Purpose: This study aims to examine the effects of human resource management (HRM) practices on organisational commitment (OC) in the Middle Eastern context. Design/methodology/approach: Survey data were collected from 493 front-line employees across a variety of industries in Jordan. A structural equation modelling analysis was performed to delineate the relationship between HRM practices and OC. Findings: A test of the model was conducted using a path analytic approach hypothesising that HRM factors influence OC. The findings indicate that the causal model is consistent with the data and contributes to a fuller understanding of the association between HRM practices and OC. Originality/value: This is the first study that represents a little-researched area of recent times and even less so in Middle Eastern countries. The findings of the study offer new perspectives on how HRM practices have direct and indirect effects on employees’ OC and would assist in reshaping the HR policies in organisations located in the Middle Eastern regions.